A new class of analytic function with measures - Pachara Chaisuriya (2018)
We introduce a new class of analytic functions on the unit disc of the complex plane by modifying the F(p, q, s) spaces introduced by the last author by adding a measure factor. We prove some basic properties and relationships with other classical function spaces. © 2013 Copyright Taylor and Francis Group, LLC.